Histiocitosis sistémica maligna en un canino. Reporte de un caso - Ochoa Amaya, Julieta E.; Roque Rodríguez, Anita; Pedraza Castillo, Natalia (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary The malignant systemic histiocytoses is a disease slightly common of dogs and cats, that has been characterize by the neoplasic proliferation of macrofhages in different organs and systems. The proliferative histiocytic disease can present nodular masses in lungs, liver, and lymphatic mediastines nodules, the dermis and epidermis are not very compromised. To the Veterinary Clinic of the Universidad de los Llanos arrived a female canine of 5 years old with depression, lack of appetite, abdominal distension, hyperventilation, purulent secretion by the vulva. With the necropsy was found a circular, multilobuled, hard, hemorrhagic mass with a diameter of 6 cm located in the cranial mediastine; in the abdominal cavity, metastases of the neoplasm to the liver and spleen. In the uterus was noticed a greater purulent secretion in the left horn. By histopathology the diagnostic was a Malignant Systemic Histiocytoses, the lungs, liver, lymph nodes and arm were affected. In the uterus was diagnosticing a pyometra.